2018
DOI: 10.3390/su10103773
|View full text |Cite
|
Sign up to set email alerts
|

Research on Catastrophic Pillar Instability in Room and Pillar Gypsum Mining

Abstract: Gypsum mines in China are mostly exploited through room and pillar mining. Due to backward mining technology and a long history of mining, a great number of pillars were left in gypsum mines. Many serious work safety accidents occurred as the result of goaf instability in history, which posed severe threats to the security of people’s lives and property. Based on the characteristics of surrounding rock damage, this research improved the constitutive equation of gypsum rock mass damage by establishing a damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Room and pillar mining methods are used in ore mines and also in coal and chemical resources mines [18,19]. Pillars of various shapes and cross-sections (continuous, square, round, rectangular) are placed between rooms.…”
Section: Room and Pillar Methods In Hard Rock Miningmentioning
confidence: 99%
“…Room and pillar mining methods are used in ore mines and also in coal and chemical resources mines [18,19]. Pillars of various shapes and cross-sections (continuous, square, round, rectangular) are placed between rooms.…”
Section: Room and Pillar Methods In Hard Rock Miningmentioning
confidence: 99%
“…The increased load may exceed the strength of adjacent pillars, and lead to their failure. Like the domino effect, rapid and large-scale collapse can be induced [4]. In addition, with the increase of mining depth, the ground stress is larger and pillar instability accidents become more frequent [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Cording observed the pillars of shale reservoirs and concluded that the instability of pillars is mainly caused by the combination of stress slabbing and slaking on the surface of pillars [8]. Based on the energy catastrophe theory, Zhou et al studied the influence of the constitutive equation and shape of the pillar in the goaf of gypsum mine on its stability and put forward the necessary and sufficient conditions for the instability of the pillar [9]. Zhou et al analyzed the influence of geometric parameters in the roof-pillar support system and obtained the classification standard of goaf stability [10,11].…”
Section: Introductionmentioning
confidence: 99%